Combined Effects of Melatonin and Citric Acid on Preservation of Fresh-cut 'Early Crisp' Pears during Cold Storage - Jingyi LÜ; Yanxia QIU; Lin BAI; Yonghong GE; Danshi ZHU; Jingxin CHEN (Shipin gongye ke-ji)
To explore the effects of melatonin (MT) combined with citric acid (CA) on preservation of fresh-cut 'Early Crisp' pears during cold storage, fresh-cut 'Early Crisp' pears were treated with 100 μmol·L−1 MT and 2% CA, alone or in combination and then stored at 4±0.5 ℃ for 9 d. Quality-related parameters, including total soluble solids (TSS) content and total colony count, were measured. Browning-related parameters, such as browning index (BI), total phenolics content, phenylalanine ammonia lyase (PAL), peroxidase (POD), and polyphenol oxidase (PPO) activities, were analyzed. Antioxidant activity-related parameters, including phenolic content, flavonoid content, ascorbic acid (AsA), and malondialdehyde (MDA) content, were measured. The 2,2-di-(4-tert-octylphenyl)-1-picrylhydrazyl (DPPH) radical and ABTS+ radical scavenging activities were evaluated during storage. The results indicated that significant differences were generally observed among all treated and untreated fresh-cut pears across the parameters considered, with the combined application of melatonin (MT) and citric acid (CA) being identified as the most effective treatment. In single treatments, the CA treatment was observed to exhibit superior anti-browning efficacy compared to the MT treatment, whereas the MT treatment was found to demonstrate higher antioxidant activity than the CA treatment. The synergistic effects of combined treatment on antioxidant activity enhancement and browning inhibition of fresh-cut 'Early Crisp' pears were observed during cold storage. At 7 days, the BI value in the combined treatment group was recorded to be 30.08%, 10.48%, and 5.41% lower than those in the control, MT, and CA treatment groups, respectively. The highest ABTS+ and DPPH radical scavenging activities were observed in the combined treatment group compared to other groups during storage. These data indicated that the MT-CA combined treatment was identified as an effective preservative for fresh-cut 'Early Crisp' pears during cold storage. This combined treatment demonstrated potential for application in food preservation.